1989
DOI: 10.1104/pp.91.4.1339
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Protein Conformational Changes in Barley Root Plasma Membrane-Enriched Microsomes

Abstract: Temperature and cations modified the reaction of barley (Hordeum vulgare L. cv Conguest) root plasma membrane protein sulfhydryl groups with N-4-(7-diethylamino-4-methylcoumarin-3-yl)-phenyl maleimide (CPM). The pseudo-first-order rate constants for the formation of fluorescent CPM-protein adducts increased as the temperature was raised above 300C, suggesting changes in protein conformation. Monovalent [K(l) It has been demonstrated with animal membrane systems that temperature-induced alterations in the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…Electrolyte leakage increased as salinity stress levels increased, indicating that salinity leads to disturbance in permeability and stability of the cellular membranes, as well as lipid peroxidation (Tajdoost et al 2007). Abiotic stresses lead to disturbance in the association between membrane lipids and proteins, which decreases enzyme activity and transport capacity of the bilayer (Caldwell & Whitman 1987). Mycorrhizal plants (except plants inoculated with G. etunicatum at soil salinity level of 4 dS m −1 ) had lower electrolyte leakage than NM control plants at different levels of soil salinity.…”
Section: Discussionmentioning
confidence: 96%
“…Electrolyte leakage increased as salinity stress levels increased, indicating that salinity leads to disturbance in permeability and stability of the cellular membranes, as well as lipid peroxidation (Tajdoost et al 2007). Abiotic stresses lead to disturbance in the association between membrane lipids and proteins, which decreases enzyme activity and transport capacity of the bilayer (Caldwell & Whitman 1987). Mycorrhizal plants (except plants inoculated with G. etunicatum at soil salinity level of 4 dS m −1 ) had lower electrolyte leakage than NM control plants at different levels of soil salinity.…”
Section: Discussionmentioning
confidence: 96%
“…As discussed above, severe drought (6-12 d) caused serious damage to thylakoid membranes and hence could increase ion leakage, implying that Ca 2+ -ATPase would be unnecessary for Ca 2+ efflux. Additionally, strong water deficit leads to a disturbance of the association between membrane lipids and proteins as well as the enzyme activity and transport capacity of the bi-layer (Caldwell and Whitman 1987). Therefore, the reduced Ca 2+ -ATPase activity under severe drought may result from the lost Ca 2+ gradient, namely the uncoupling effect of water stress on chloroplasts (Younis et al 1979).…”
Section: Discussionmentioning
confidence: 97%
“…The reduction in photophosphorylation activity under heavy drought was due to thylakoid membrane conformational changes (Fig. 2) (Fellows and Boyer 1976). It is easy to conclude that the decline in ATP content under severe drought could be due to reductions in Ca 2+ -ATPase and photophosphorylation activities (Younis et al 1979, Tezara et al 1999.…”
Section: Discussionmentioning
confidence: 98%
“…Senescence is an active programmed phenomenon, yet it could be accelerated by exogenous factors (Brooks et al 1982, Caldwell and Whitman 1987, Kramer 1983, Mayak et al 1983). In wheat ears senescence is triggered after anthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Others authors also have reported changes in the lipid/protein ratio of the membrane and in enzyme structure, as in various proteases and lipases (Caldwell andWhitman 1987, Noodén andGuiamet 1996). It has been postulated that the breakdown of the lipid/protein configuration of the membrane is promoted by the lipid peroxidation caused by free radicals (Paulin et al 1986).…”
mentioning
confidence: 99%